Upaya Meningkatkan Daya Pengelolaan SDM Di Era Digital Pada Atan Export - Rida Utami; Nahar Maganda Saragih; Irham Aksa (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2023)
Digitalization of HR The board is the utilization of data innovation in the use of data and information the executives connected with HR in an organization or association. HR is the fundamental key being developed in all fields, including the oceanic and fisheries area. HR are accessible labor supply, including their number and information, abilities, and capacities. One might say that the nature of HR is one of the deciding variables in making the progress of an improvement program. In this way, the improvement of the quality and amount of HR is earnestly required with the goal that the usage of marine and fishery assets is completed ideally. What's more, so Indonesia has marine and fisheries faculty who are professional and of public and global principles to create great oceanic security. Atan Commodity is an organization that requires HR for the advancement of an administration of product and imported merchandise in the computerized world, thus dealing with the advanced period is vital to propel this organization.